Huygens's principle for the wave equation for second-rank tensor fields - Noonan, Thomas W. (The Astrophysical journal, 1989)
The differential equations for the Green's function for the wave equation of a second-rank tensor field are expanded in Robertson's geodesic coordinates about the vertex of the backward null cone as in a previous paper for the vector wave equation. It is concluded that Huygens' principle is satisfied, subject to the special-relativity postulate, if and only if the spacetime is flat. Two physical fields to which this result may be applied are the electromagnetic field tensor and the linear approximation to the gravitational field.